Tesl trainees focus in types of questions used for teaching reading comprehension during their teaching practice - Siti Noor Suzanni, Ab. Rahman. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study was conducted to investigate the TESL trainees focus in types of questions used for teaching reading comprehension during their teaching practice. It was aim to find out the question type used by the trainees, frequency of each question type be used and the amount for each type of question used by trainees for teaching reading comprehension during their teaching practice. The sample participants for this study consisted of 22 trainees which each of them given one lesson plan specifically on teaching reading comprehension. Data for this study was based on the lesson plans analysis. The findings showed that the main comprehension question that used by TESL trainees in teaching reading comprehension during their teaching practice was literal comprehension. TESL trainees frequently used this question type as most comprehension tests focus on literal comprehension and required students to recall only fact from the text because it is the easiest to test students’ understanding on the text that they read.